2019
DOI: 10.1101/766873
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms that allow cortical preparatory activity without inappropriate movement

Abstract: 32We reveal a novel mechanism that explains how preparatory activity can evolve in motor-related 33 cortical areas without prematurely inducing movement. The smooth eye movement region of the 34 frontal eye fields (FEFSEM) is a critical node in the neural circuit controlling smooth pursuit eye 35 movement. Preparatory activity evolves in FEFSEM during fixation in parallel with an objective 36 measure of visual-motor gain. We propose that the use of FEFSEM output as a gain signal 37 allows for preparation to pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Although we consider SC activity during the delay period to be preparatory in the sense that it is related to the enhancement or hindrance of rapid saccade initiation following the go cue, it does not have “motor potential.” In the smooth pursuit system of the FEF, neural activity was found to have motor potential, with partially overlapping subpopulations contributing to both the preparation and execution of movement (Darlington and Lisberger, 2020). However, this does not seem to be the case for the SC, at least in the context of saccades.…”
Section: Discussionmentioning
confidence: 99%
“…Although we consider SC activity during the delay period to be preparatory in the sense that it is related to the enhancement or hindrance of rapid saccade initiation following the go cue, it does not have “motor potential.” In the smooth pursuit system of the FEF, neural activity was found to have motor potential, with partially overlapping subpopulations contributing to both the preparation and execution of movement (Darlington and Lisberger, 2020). However, this does not seem to be the case for the SC, at least in the context of saccades.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported an elevated spontaneous activity of FEF neurons toward saccade onset or smooth pursuit onset, which was more pronounced than what we observed here. Those studies typically let the subjects decide when to saccade 32 or anticipate the speed of the upcoming tracking target 40 , 41 . In those cases, spontaneous activity naturally represented the decision processes or prediction of a feature rather than temporal expectations.…”
Section: Discussionmentioning
confidence: 99%
“…In the pursuit system, motor preparation modulates the state of visual-motor gain (Kodaka & Kawano, 2003; Tabata et al, 2006). Preparatory enhancement of visual-motor gain has been linked to FEF SEM neurons, which display preparatory ramps of firing during fixation that leads up to pursuit (Darlington & Lisberger, 2020; Mahaffy & Krauzlis, 2011; Tanaka & Fukushima, 1998). Expectation of faster target motion causes larger amplitudes of preparatory activity and larger behavioral readouts of visual-motor gain (Darlington et al, 2018; Darlington et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Visual-motor gain and FEF SEM have been implicated in many higher-order features of pursuit, for example reward (Raghavan & Joshua, 2017), motor learning (Li & Lisberger, 2011), and modulation of behavior by experience-dependent expectation of target motion (Darlington et al, 2018). Importantly, both visual-motor gain and preparatory activity in FEF SEM are dialed up in preparation for smooth pursuit eye movements (Darlington & Lisberger, 2020; Tabata et al, 2006). It is possible to probe visual-motor gain by measuring the eye movement responses to brief pulses of target motion.…”
Section: Introductionmentioning
confidence: 99%